Histopathological assessment of acetaminophen-induced liver injury and regeneration response following edible bird’s nest administration in ICR and BALB/C mice model - Fazil, Muhammad Azam (2021)
Acetaminophen (APAP) overdose is known to induce liver injury in mice models and humans. Excessive accumulation of reactive metabolite, N-acetyl-p-benzoquinone-imine (NAPQI) increases oxidative stress in tissues, leading to centrilobular necrosis after exceeding the glutathione (GSH) threshold. Although liver recovery takes place after clearance of toxic insults, however, the degree of hepatic regeneration differs between mice strains. Therefore, the first aim of the study was a comparative assessment of APAP-induced liver injury (AILI) and subsequent hepatic regeneration of two mouse models (ICR and BALB/c). Meanwhile, edible bird’s nest (EBN) is a well-known natural product with various health-enhancing properties including anti-oxidative and cell proliferative effects. However, the role of EBN from a toxicological perspective against APAP toxicity is lacking. Hence, the second objective aimed to assess the prophylactic and regenerative effect of EBN on AILI response in ICR mice. These studies hypothesized that both models respond differently, and self-regenerating hepatocytes could be prompted by prophylaxis EBN. For the first objective, 25 ICR and 20 BALB/c mice were grouped as controls and treatments of 5, 10, 24, and 48 hours post-APAP dosing (hpd) with 5 animals per each. Secondly, 80 ICR mice were assigned to groups of control, APAP (500 mg/kg) and seven days prophylactic of silymarin (200 mg/kg), and EBN (60, 120, and 250 mg/kg) followed by an APAP induction. Livers were harvested for histopathological assessment by haematoxylin and eosin (H&E) staining and proliferating cell nuclear antigen (PCNA) using immunohistochemistry. Results of the first experiment showed that APAP-treated BALB/c mice had an intense hepatocellular injury at 5 hpd than ICR mice that only exhibited damage at 10 hpd before both underwent almost complete regeneration after 24 hpd. The second study revealed significant differences in histological changes between APAP and prophylactic treatment groups at 10 hpd, with complete recovery of all groups observed at 24 hpd except for EBN 250 that sustained injuries. Hepatocytes proliferation was initiated at 5 hpd in silymarin, EBN 60 and EBN 120, while at 24 hpd, EBN 120 and 250 exhibited higher PCNA expressing hepatocytes. The hepatoprotective role was observed earlier in silymarin, EBN 60 and 120, while cellular proliferation was delayed in EBN 250. In conclusion, all groups showed liver recovery after clearance of APAP insult at later time points but EBN 60 and 120 enhanced the hepatic proliferation as similar to silymarin. Therefore, this proves EBN 60 and 120 could act as prophylaxis liver supplements to accelerate the hepatic regeneration in AILI.